THE COVID-19 PANDEMIC ERA: THE EFFECTIVENESS OF GOOGLE CLASSROOM MEDIA IN DISCRETE MATHEMATICS LEARNING IN TERMS OF STUDENT LEARNING OUTCOMES - Justin Eduardo Simarmata; Ferdinandus Mone (MES: Journal of Mathematics Education and Science, 2021)
One of the learning media in the network that is often used in addressing various learning problems during the Covid-19 pandemic is the use of google classroom media. The purpose of this study is to find out the effectiveness of google classroom media in discrete mathematics learning in terms of learning outcomes. The type of research conducted is quasi experiment research to see the consequences of a treatment by comparing the learning outcomes of two class groups (independent class) or two time groups with the same class (dependent class). The research design is applied using one group pretest-posttest design. The samples in this study were all the fourth semester class A students who took discrete mathematics courses at the S1 level of the Mathematics Education Study Program of the Faculty of Education, Timor University which consisted of 40 students. Sample data was processed with descriptive analysis and average difference test using paired sample t test and N-Gain Score. The research results showed that learning outcomes by using google classroom media is quite effective based the students’ test results. The students’ learning outcomes after learning by applying google classroom media were higher than students’ learning outcomes before learning by applying google classroom media.